PENGARUH PARAMETER PENGONTROL DALAM MENEKAN PENYEBARAN PENYAKIT FLU BURUNG - Rina Reorita; Niken Larasati; Renny Renny (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2011)
Indonesia has been being a country which has the most victims of avian influenza case. Avian influenza is caused by influenza virus H5N1 type. This virus can be transmitted from infected poultry to susceptible poultry and infected poutry to susceptible human. This paper describes an SIR (Susceptible, Infection, Recovery) mathematic model for the spread of avian influenza disease. The basic reproduction number will be obtained for analyzing what are the factors that can influence the epidemic. By the Pontryagin Maximum Principle, it can be seen how is the influence of vaccine as a control to the spread of disease.